Effects of different manganese sources on nutrient digestibility, fecal bacterial community, and mineral excretion of weaning dairy calves - Ji, Huimin; Tan, Dejin; Chen, Yuhua; Cheng, Zhiqiang; Zhao, Jingwen; Lin, Miao (Frontiers in Microbiology, 2023)
The aim of this study was to clarify the effects of different manganese (Mn) sources in the basal diets on nutrient apparent digestibility, fecal microbes and mineral elements excretion before and after weaning. Fifteen Holstein heifer calves (6-week-old, 82.71 ± 1.35, mean ± standard error) were randomly designed into three group (5 each): no extra Mn supplemented (CON), 20 mg Mn/kg (dry matter basis) in the form of chelates of lysine and glutamic acid in a mixture 1:1 (LGM), and 20 mg Mn/kg (dry matter basis) in the form of MnSO4. All calves were weaned at 8 weeks of age. The experiment lasted for 28 days (14 days before weaning and 14 days after weaning). Dry matter intake (DMI) were recorded daily. The animals were weighed by electronic walk-over and body size indices were collected using tape on day -14, -1 and 14 of weaning. The faeces of calves were collected to measured apparent digestibility of nutrients (acid insoluble ash was internal marker) and bacterial community on day -1, 1, 3, 7 and 14 of weaning. Fecal minerals concentration was determined by inductively coupled plasma emission spectroscopy on day -1, 1, 7 and 14 of weaning. The results showed that, compared to the CON group, LGM addition increased the apparent digestibility (P < 0.05). The Chao 1 and Shannon index of fecal bacterial decreased at day 1 in LGM and MnSO4 groups and increased after weaning. The PCoA results indicated that the LGM group was distinctly separate from the CON and MnSO4 groups during the whole experimental period. Significant differences (P < 0.05) were observed in the relative abundance of two phyla (Proteobacteria and Spirochaetota) and eight genera (Alloprevotella, Prevotellaceae_UCG-001, Clostridia UCG 014, RF39, UCG-010, Pseudomonas, Ralstonia and Treponema) in three groups. Moreover, LGM group showed less excretion of Fe, P and Mn than MnSO4 group. In summary, 20 mg Mn/kg diet supplementation improved the nutrient digestibility, changed the fecal microbial community, and reduced the mineral excretion. Organic Mn supplementation in the diet had more advantage over the sulfate forms in weaning calves.